PENERAPAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) BERBANTUAN LKPD TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS IV SD NEGERI 34 LUBUKLINGGAU - Anggreani, Ayu; Purwasi, Lucy Asri; Mandasari, Novianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to find out whether the mathematical problem solving abilities of class IV students at SD Negeri 34 Lubuklinggau after applying the Indonesian Realistic Mathematics Education (PMRI) approach assisted by LKPD are significantly categorized as good. The research method used was Pre-Experimental Design with a one-group pretest-posttest design category. The population and sample or research subjects were class IV consisting of 25 students. The data collection technique used is a test technique, namely a pre-test and post-test. Data analysis technique with stages: problem solving ability value, average value and standard deviation, normality test, and z-test. The results of the research using the z-test with a significance level of 5% obtained Zcount (2.86) ≥ Ztable (1.64). The conclusion is that the average value of the mathematical problem solving ability of class IV students at SD Negeri 34 Lubuklinggau after applying the Indonesian Realistic Mathematics Education (PMRI) approach assisted by LKPD is significantly in the good category.